Análise de desempenho de um fogão solar construído a partir de sucatas de antena de tv - Ramos Filho, Ricardo Eugênio Barbosa (2011)
Given the growing environmental crisis caused by degradation, mainly due to the use of polluting energy sources, increasing the growing use of renewable energies worldwide, with emphasis on solar energy, an abundant supply and available to everyone, which can be harnessed in several ways: electricity generation; dehydration of food; heating, disinfection and distillation and cooking. The latter has as its primary feature the viability of clean, renewable energy for society, combating ecological damage caused by large-scale use of firewood for cooking foods, use in tropical countries with high solar radiation, and has funding NGOs throughout the world with the goal of achieving low-income population. The proposed project consists of a solar cooker for concentration, working from the reflection of sunlight by a hub that they converge to a focal point at the bottom of the pot, getting lots of heat. The solar cooker under study consists of two elliptical reflecting parabolas made from the recycling of scrap TV antenna, having 0.29 m² of surface area for each antenna, which were covered by multiple mirrors of 2 mm thick and mounted on a metal structure, with correction for the mobility of the apparent movement of the sun. This structure was built with the recycling of scrap metal, possessing a relatively low cost compared with other solar cookers, around US$ 50.00. This cost becomes negligible, since that will involve a great benefit to not have fuel costs for each meal, unlike the use of gas or firewood for cooking food. The tests show that the cooker has reached the maximum temperature of 740 ° C, for boiling water in an average time of 28 minutes, cooking various types of foods such as potatoes, rice and pasta in an average time of 45 minutes and still going as a solar oven, making pizza baking and meat. These cooking times do not differ much from the cooking times on a gas stove, it becomes the solar cooker as a good consumer acceptance, and furthermore not to deliver the same gases that can poison the food as with the wood stove. Proves the viability of using the stove to cook or bake in two daily meals for a family, still presenting a position to improve his performance with the addition of new materials, equipment and techniques